Influence of the apical enlargement size on the endotoxin level reduction of dental root canals (Journal of Applied Oral Science, 2012)
Gram-negative bacteria play an essential role in endodontic infections because they have virulence factors such as endotoxin. Due to its potential cytotoxic activity, special attention has been given to the removal/neutralization of this endotoxin in the root canal system. OBJECTIVE: The aim of this study was to evaluate the influence of the apical enlargement size (AES) by using rotary instruments on the endotoxin level reduction of dental root canals. MATERIAL AND METHODS: Forty root canals of the mandibular premolar teeth were used. Escherichia coli endotoxin (055: B55) was inoculated into thirty root canals. Ten teeth served as the negative control group. After the incubation period, the first endotoxin samples were collected from the root canals with a sterile/apyrogenic paper point for the analysis of the endotoxin units (EU/mL) present before instrumentation (S1). Specimen instrumentation was performed with the Mtwo® rotary system in the sequence 10/.04, 15/.05, 20/.06, 25/.06, 30/.05, 35/.04 and 40/.04. To monitor the effectiveness of increasing apical enlargement on endotoxin removal, the second endotoxin samples were collected from all the root canals after instrumentation with the following instruments: #25/.06- (S2); #30/.05- (S3); # 35/.04- (S4); and #40/.04- (S5). Limulus amebocyte lysate (LAL) was used to quantify the levels of endotoxin. The results were statistically compared by using repeated measures of ANOVA with post hoc Tukey testing. RESULTS: Increasing levels of endotoxin removal was achieved by large sized apical enlargement: S2 (AES #25/.06)- 89.2%, S3 (AES #30/.05)- 95.9%, S4 (AES #35/.04)- 97.8% and S5 (AES #40/.04)- 98.2%. Substantial reduction of endotoxin content was obtained in S4 and S5 compared to S2 (p